The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/2516-1075/ababde
|View full text |Cite
|
Sign up to set email alerts
|

Robust mixing in self-consistent linearized augmented planewave calculations

Abstract: We devise a mixing algorithm for full-potential (FP) all-electron calculations in the linearized augmented planewave (LAPW) method. Pulay’s direct inversion in the iterative subspace is complemented with the Kerker preconditioner and further improvements to achieve smooth convergence, avoiding charge sloshing and noise in the exchange–correlation potential. As the Kerker preconditioner was originally designed for the planewave basis, we have adapted it to the FP-LAPW method and implemented in the exciting code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In the previous Section 2.2 the interstitial Yukawa potential is used as boundary values for the Yukawa potential in the atomic spheres. This subsection is concerned with the construction of the Fourier transformable pseudo-charge density ρ α that replaces the true local charge density ρ α [see (11)] inside the muffin-tin sphere such that the Yukawa potential in the interstitial region,…”
Section: Interstitial Yukawa Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous Section 2.2 the interstitial Yukawa potential is used as boundary values for the Yukawa potential in the atomic spheres. This subsection is concerned with the construction of the Fourier transformable pseudo-charge density ρ α that replaces the true local charge density ρ α [see (11)] inside the muffin-tin sphere such that the Yukawa potential in the interstitial region,…”
Section: Interstitial Yukawa Potentialmentioning
confidence: 99%
“…By solving Eq. 1 for general periodic densities, the Kerker preconditioner [9] can be extended to density functional methods of general densities [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…They were originally devised for planewave based methods. Recent theoretical studies have shown a formulation of the Kerker preconditioner as well as its implementation in full-potential (FP) calculations with the linearized augmented planewave (LAPW) basis set [26,27]. The Resta preconditioner, however, is not yet reformulated to implement in the FP-LAPW method.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, strong fluctuations in ρ out i caused by a small change of ρ in i prevent the convergence during the self-consistency iteration. This phenomenon is well-known as charge sloshing [17][18][19][20][21][22][23][24][25][26][27], which is more severe in metals with large supercells. To avoid this problem, one can add an effective preconditioner in Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation